Grundlagenwissenschaftliche Untersuchung der kombinierten Prozesskette aus Umformen und Additive Fertigung - Schaub, Adam (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)
Nowadays, a rising amount of individualized products is requested due to a highly industrialized mankind with growing individual identities. Moreover, our generation faces the challenge of a cost, resource, and time efficient production of goods. One promising manufacturing approach to fulfill these needs is additive manufacturing. Though, additive manufacturing is also subject to some limitations such as a high amount of manufacturing time as well as limited efficiency of the power source. To overcome these disadvantages and to produce individual products a process chain combining conventional manufacturing techniques with conventional manufacturing techniques is presented within this work. The aim is to propound and analyze a process chain which fulfills today’s challenges of sustainable production. Within a determined process chain forming is combined with successive additive manufacturing to produce hybrid metallic parts. Therefore, laser and electron beam melting are investigated as well as various forming technologies such as bending, deep drawing and super plastic forming. As basis of this work these manufacturing technologies are analyzed with focus on their applicability and benefits for the combined process chai